2002
DOI: 10.1038/sj.bdj.4801538
|View full text |Cite
|
Sign up to set email alerts
|

Disability Part 2: Access to dental services for disabled people. A questionnaire survey of dental practices in Merseyside

Abstract: This article aims to identify how accessible general dental practitioners thought that their services were and to identify the barriers they face in providing care for disabled people. A postal questionnaire survey was undertaken of all general dental practices in the Liverpool, Sefton, St Helens and Knowsley Health Authorities. Only one quarter of practices described themselves as having full physical access for disabled patients. However, despite this, over 90% of practices reported treating disabled patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
26
0
2

Year Published

2002
2002
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 6 publications
1
26
0
2
Order By: Relevance
“…In the past, research has suggested that dentists have found this population stressful or too challenging to treat (11,12,22,69,(71)(72)(73)(74), and 76% of general dentists in one study reported finding it difficult to provide treatment for people with disabilities (71). Dentists may feel the pressures of time and that inadequacy of reimbursements creates disincentives to treat these populations (71,(75)(76)(77). Additionally, they may feel ill at ease when faced with human diversity or be concerned that they may have to reduce the technical quality of care for patients with reduced cooperation (69,74,78).…”
Section: Prevalence Of Disability Worldwidementioning
confidence: 99%
“…In the past, research has suggested that dentists have found this population stressful or too challenging to treat (11,12,22,69,(71)(72)(73)(74), and 76% of general dentists in one study reported finding it difficult to provide treatment for people with disabilities (71). Dentists may feel the pressures of time and that inadequacy of reimbursements creates disincentives to treat these populations (71,(75)(76)(77). Additionally, they may feel ill at ease when faced with human diversity or be concerned that they may have to reduce the technical quality of care for patients with reduced cooperation (69,74,78).…”
Section: Prevalence Of Disability Worldwidementioning
confidence: 99%
“…3 Physical, social and information are barriers that impact on oral health of visual impairment. 4 Visual impairments tended to have a larger amount of dental plaque and were at a higher risk for dental diseases than were sighted individuals. 5 Oral health and dental care of the disabled has generally been poorer than the general population.…”
Section: Introductionmentioning
confidence: 99%
“…In a recent study in MS, 72% of dental professionals report having no training when it comes to wheelchair transfers [15]. Surprisingly, few dental clinics are actually accessible to the disabled despite the guidelines set forth by the Americans with Disabilities Act (ADA) [22].…”
Section: Introductionmentioning
confidence: 99%